Uncertainty quantification in theoretical spectroscopy: The structural sensitivity of X‐ray emission spectra. Issue 2 (26th August 2017) - Oung, Sangwar Wadtey; Rudolph, Julian; Jacob, Christoph R.
Abstract: We present a methodology for analyzing the dependence of molecular spectra calculated with quantum‐chemical methods on the underlying molecular structure. This analysis is applied to investigate the structural sensitivity of calculated valence‐to‐core X‐ray emission (VtC‐XES) spectra for the test case of three iron carbonyl complexes, Fe(CO)5, [FeCp(CO)2 (THF)] + (Cp = cyclopentadienyl, THF = tetrahydrofuran), and Fe(CO)3 (cod) (cod = cyclooctadienyl). Based on this analysis, we discuss how the VtC‐XES spectra depend on changes of metal–ligand bond distances and bond angles as well as on the structure of the ligands. The benefits of such an analysis of the structural sensitivity are discussed. Our methodology can serve as a first step toward quantifying and accounting for uncertainties due to the underlying model structure in theoretical spectroscopy. Abstract : Quantum‐chemical calculations of spectra are essential for the elucidation of molecular structures, but are prone to unavoidable errors of the underlying methodology. As a first step toward accounting for uncertainties in theoretical spectroscopy, a methodology for assessing the sensitivity of calculated spectra on the underlying molecular structure is presented and applied to the valence‐to‐code X‐ray emission spectra of iron carbonyl complexes.